2017
DOI: 10.1002/uog.15924
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum two‐ and three‐dimensional ultrasound evaluation of anal sphincter complex in women with obstetric anal sphincter injury

Abstract: 2D-TPUS and 3D-EVUS are not accurate modalities for the assessment of anal sphincters after repair of OASIS. 3D-TPUS shows good agreement with the gold standard 3D-EAUS and a high sensitivity in detecting residual defects. It, thus, has potential as a screening tool after primary repair of OASIS. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
6
17
2
1
Order By: Relevance
“…Contrary to Ros et al, we also found a weak significant association between TPUS score and Wexner score. Our results revealed that it was the EAS score rather than the IAS score, for both EAUS and TPUS, that constituted the body of correlation.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to Ros et al, we also found a weak significant association between TPUS score and Wexner score. Our results revealed that it was the EAS score rather than the IAS score, for both EAUS and TPUS, that constituted the body of correlation.…”
Section: Discussioncontrasting
confidence: 99%
“…In concordance with Ros et al, our coefficients of correlation between EAUS and TPUS were almost identical, with a correlation coefficient of 0.72 vs 0.76 for defects in the EAS and 0.66 vs 0.65 for defects in the IAS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations